CASE STUDY OF THE LOCAL WISDOM OF THE BADUY TRIBE IN PRESERVING THE RIVER - Wahid Dzulhaji; Nur Fadhilah Awaliyah; Muhammad Faisal Fahrudin Firdaus; Eneng Liah Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2025)
The natural philosophy of the Baduy people is very strong. The Baduy people strongly maintain balance and harmony with nature. As a result, they strongly defend the teachings about protecting and preserving nature. That is what makes the Baduy people coexist with nature in harmony. In addition, the Baduy people do not exploit natural resources; Instead, they use what is available with preservation. The Baduy people have the belief that nature is one of the almighty trusts that must be maintained and preserved. This is in accordance with the teaching and philosophical principles of the Baduy tribe, namely